Pregnancy Outcomes in Women With a History of Previable, Preterm Prelabor Rupture of Membranes. Issue 2 (June 2017) - Monson, M.A.; Gibbons, K.J.; Esplin, M.S.; Manuck, T.A.
Abstract : (Obstet Gynecol . 2016;128(5):976–982) About one third of preterm births is caused by preterm prelabor rupture of membranes (PPROM), which is a complication that occurs in about 3% to 4.5% of all pregnancies. The objective of this study was to describe subsequent pregnancy outcomes among women who had a history of PPROM at <24 weeks of gestation. The study also evaluated the use of various prophylaxis modalities during preterm birth.